Optimization of Mechanical Properties of Rotary Friction Welding (RFW) Joints in AISI 1008 Steel with Friction Time Variation - Yustiasih Purwaningrum; Rachnaldy Putra; Excel Rifky Fachreza (JRST (Jurnal Riset Sains dan Teknologi), 2025)
One method than can be used to joint solid cylinders is Rotary Friction Welding (RFW). RFW is a Type solid-state welding that has the advantage of not requiring filler, shielding gas and produces good mechanical properties because the joining occurs below the base metal temperature. This study aims was to determine the effect of friction time on the physical and mechanical properties of Rotary Friction Welding (RFW) joints in AISI 1008 steel. RFW welding is carried out with a rotation speed of 1,170 RPM and friction plunge of 3 mm and forging depth 2 mm with three kinds of welding time, 3 minutes, 4 minutes and 5 minutes were investigated.  The average temperature of RFW welding with variations of welding time (3-minute, 4-minute and 5-minute) are 1,022.3°C, 1034.5°C and 1,062.7°C. The physical properties of the weld joint were obtained from photomacro using an optical microscope and corrosion testing using the weight loss method. The mechanical properties of the RFW weld joint were determined from tensile and bending tests using a Universal Testing Machine as well as hardness testing using the Vickers Microhardness method. Photomacro observations show that the longer the welding time used in RFW welding, the wider the welded area. The test results show that optimal physical and mechanical properties were obtained on RFW weld joints with a welding time variation of 4 minutes. At the 4-minute variation, the highest tensile and bending strength values were obtained compared to other time variations. As for the hardness testing of the welding zone with a friction  time of 4 minutes, it has the smallest value compared to other variations in welding time (3 minutes and 5 minutes). For the base metal and the HAZ, the hardness values for all variations are relatively the same because the materials used are the same and the welding heat is not high enough to change the microstructure in the area. Corrosion testing conducted for 50 days showed that all RFW welds with welding time variations had excellent corrosion resistance values.